(untitled) (PANGEEA, 2025)
Alba County is a tourist area of great interest to the traveler found out in searching for a past ancient testimony, expressed by numerous historic monuments, of the architecture and art, through a variety of natural reservations in single country, even in world, by special landscapes the Apuseni Mountains, Sebeş Mountains, but of lush lowlands Mureş Târnave and Ampoi.